2011
DOI: 10.1159/000327821
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin E Administration on the Elevated Oxygen Stress and the Telomeric and Subtelomeric Status in Alzheimer’s Disease

Abstract: Background: Oxidative stress (OS) may be involved in the neurodegenerative process in Alzheimer’s disease (AD). Telomeres, the repeated sequences that cap chromosome ends, undergo shortening with each cell division, are sensitive to OS, and serve as markers of a cell’s replicative history. Telomere length shortening has been reported to relate to OS with aging process and aging-associated diseases, but the telomeric changes were not always identical, especially in change of telomere length distribution and sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 98 publications
0
32
0
2
Order By: Relevance
“…39 In addition, a study in a Chinese population with similar age range of participants as our study reported that the LTL was generally less than 12,000 bp. 40 The association between HCY and telomeres was first explored by Bekaert et al in 2007 as part of a study in a Belgian cohort aimed at investigating the link between CVD risk markers and LTL. 15 However, an association between LTL and CVD risk markers, including cholesterol, TGs, blood pressure, and plasma HCY, was not found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 In addition, a study in a Chinese population with similar age range of participants as our study reported that the LTL was generally less than 12,000 bp. 40 The association between HCY and telomeres was first explored by Bekaert et al in 2007 as part of a study in a Belgian cohort aimed at investigating the link between CVD risk markers and LTL. 15 However, an association between LTL and CVD risk markers, including cholesterol, TGs, blood pressure, and plasma HCY, was not found.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the remaining 90 samples were included in this study because TL < 2000 bp is normally found in individuals above 80 years, 39 and this exclusion criteria was also based on the range reported in Chinese populations (generally longest < 12,000 bp). 40 …”
Section: Telomere Length Measurementmentioning
confidence: 99%
“…It is relevant that both ascorbic acid (vitamin C) and tocopherol (vitamin E) are recognized antioxidants [116][117][118][119] that can prevent ROS generation, therefore increasing oxidative stress. For patients with Alzheimer's disease, elevated oxidative stress levels were found, besides shorter telomeres [120]. When vitamin E was administered to these patients, although there was no significant difference in telomere length after 6 months, levels of oxidative stress were lower [120].…”
Section: What Can Be Done To Help Maintain Telomere Length?mentioning
confidence: 88%
“…For patients with Alzheimer's disease, elevated oxidative stress levels were found, besides shorter telomeres [120]. When vitamin E was administered to these patients, although there was no significant difference in telomere length after 6 months, levels of oxidative stress were lower [120].…”
Section: What Can Be Done To Help Maintain Telomere Length?mentioning
confidence: 88%
“…Additionally, TL is associated with lifestyle choices such as diet, tobacco and alcohol use [12], physical activity, and sleep [3]. Fewer studies have focused on the dynamic change and regulation of TL by implementing exercise programs [13,14], vitamin supplements [15], diet [16], meditation [17], and genetic engineering [18]. Interest in telomere lengthening or length maintenance is due to the notion that this will serve to slow down or cease a person's biological clock providing youthfulness and health longevity [10].…”
Section: Introductionmentioning
confidence: 99%